A quality‐of‐life questionnaire for heavy menstrual bleeding in Thai women receiving oral antithrombotics: Assessment of the translated Menstrual Bleeding Questionnaire. Issue 7 (10th November 2021) - Rodpetch, Tinaram; Manonai, Jittima; Angchaisuksiri, Pantep; Boonyawat, Kochawan
Abstract: Background: Heavy menstrual bleeding (HMB) is common among reproductive‐aged women receiving oral antithrombotics and frequently results in a negative impact on quality of life. Methods: We translated the Menstrual Bleeding Questionnaire (MBQ) into Thai by forward translation, back‐translation, pretesting, and cognitive interviewing. The translated questionnaire was content validated by a gynecologist. A validation study was conducted for the translated MBQ and defined the optimal score for the diagnosis of HMB. We then performed a cross‐sectional study to determine the prevalence of HMB using the translated MBQ. Reproductive‐aged Thai women who visited outpatient clinics receiving oral antithrombotics were asked to assess menstrual characteristics after receiving antithrombotics. The impact of menstruation on quality of life was assessed by using the MBQ. Results: The translated MBQ had excellent reliability (intraclass correlation coefficient = 0.93) and discriminated between women with and without HMB (area under the receiver operating characteristic curve = 0.93). A score of 21.5 had 82.9% sensitivity and 83.1% specificity in the diagnosis of HMB. The mean (standard deviation) of the score was significantly higher in the HMB group than in the normal menstrual bleeding group (30.4 [9.4] vs 15.4 [5.6]; P < .001, respectively). Of the 49 women, the prevalence of HMB in patients receiving warfarin (n = 29), direct oral anticoagulants (n = 4), or antiplatelet agents (n = 16) was 27.6%, 25.0%, and 25.0%, respectively. Conclusions: MBQ is a simple and valid tool that can be applied to screen women experiencing HMB. One‐fourth of reproductive‐aged women who received oral antithrombotics experienced HMB that impacted their quality of life.